Neostigmine Attenuates Proinflammatory Cytokine Expression in Preoptic Area but Not Choroid Plexus during Lipopolysaccharide-Induced Systemic Inflammation - Andrzej P. Herman; Dorota Tomaszewska-Zaremba; Marta Kowalewska; Aleksandra Szczepkowska; Małgorzata Oleszkiewicz; Agata Krawczyńska; Maciej Wójcik; Hanna Antushevich; Janina Skipor (Mediators of Inflammation)
The study was designed to examine whether the administration of neostigmine (0.5 mg/animal), a peripheral inhibitor of acetylcholinesterase (AChE), during an immune/inflammatory challenge provoked by intravenous injection of bacterial endotoxin—lipopolysaccharide (LPS; 400 ng/kg)—attenuates the synthesis of proinflammatory cytokines in the ovine preoptic area (POA), the hypothalamic structure playing an essential role in the control of the reproduction process, and in the choroid plexus (CP), a multifunctional organ sited at the interface between the blood and cerebrospinal fluid in the ewe. Neostigmine suppressed (p<0.05) LPS-stimulated synthesis of cytokines such as interleukin- (IL-) 1β, IL-6, and tumor necrosis factor (TNF) α in the POA, and this effect was similar to that induced by the treatment with systemic AChE inhibitor—donepezil (2.5 mg/animal). On the other hand, both AChE inhibitors did not influence the gene expression of these cytokines and their corresponding receptors in the CP. It was found that this structure seems to not express the neuronal acetylcholine (ACh) receptor subunit alpha-7, required for anti-inflammatory action of ACh. The mechanism of action involves inhibition of the proinflammatory cytokine synthesis on the periphery as well as inhibition of their de novo synthesis rather in brain microvessels and not in the CP. In conclusion, it is suggested that the AChE inhibitors incapable of reaching brain parenchyma might be used in the treatment of neuroinflammatory processes induced by peripheral inflammation.